Densities of ethyl esters produced from different vegetable oils - Baroutian, S.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (American Chemical Society, 2008)
Biodiesel density data as a function of temperature is needed to model the combustion process. In this work, the densities of ethyl ester biodiesel obtained from various vegetable oils were measured at various temperatures from (15 to 90) degrees C. The data obtained were used to validate the method proposed by Spencer and Danner using a modified Rackett equation. The experimental and estimated density values using the modified Rackett equation gave almost identical values with deviations less than (0.21, 0.35, 0.22, 0.15, and 0.24) for the ethyl esters of palm, soybean, canola, corn, and ricebran oil, respectively. Simple linear equations for density of various vegetable oil ethyl ester biodiesels are also proposed in this work.